In Vitro Biological Performance of Alginate Hydrogel Capsules for Stem Cell Delivery - de Souza, Jaqueline Brandão; Rosa, Gustavo dos Santos; Rossi, Mariana Correa; Stievani, Fernanda de Castro; Pfeifer, João Pedro Hübbe; Krieck, André Massahiro Teramoto; Bovolato, Ana Lívia de Carvalho; Fonseca-Alves, Carlos Eduardo; Borrás, Vicente Amigó; Alves, Ana Liz Garcia (Frontiers in Bioengineering and Biotechnology, 2021)
Encapsulation of biological components in hydrogels is a well described method for controlled drug delivery of proteins, tissue engineering and intestinal colonization with beneficial bacteria. Given the potential of tissue engineering in clinical practice, this study aimed to evaluate the feasibility of encapsulation of adipose tissue-derived mesenchymal stem cells (MSCs) of mules in sodium alginate. We evaluated capsule morphology and cell viability, immunophenotype and release after encapsulation. Circular and irregular pores were observed on the hydrogel surface, in which MSCs were present and alive. Capsules demonstrated good capacity of absorption of liquid and cell viability was consistently high through the time points, indicating proper nutrient diffusion. Flow cytometry showed stability of stem cell surface markers, whereas immunohistochemistry revealed the expression of CD44 and absence of MHC-II through 7 days of culture. Stem cell encapsulation in sodium alginate hydrogel is a feasible technique that does not compromise cell viability and preserves their undifferentiated status, becoming a relevant option to further studies of tridimensional culture systems and in vivo bioactive agents delivery.